Can accelerated partial breast irradiation be a treatment standard? - Gisterek, Iwona; Szelachowska, Jolanta; Kornafel, Jan (Contemporary Oncology/Współczesna Onkologia, 2009)
Accelerated partial breast irradiation (APBI) as part of breast conserving therapy (BCT) of early breast cancer is being investigated in several phase III trials at the present time. Different techniques of brachytherapy and external beam therapy are compared in terms of their possible benefits and pitfalls. The aim of the discussion is to appropriately select for this therapy a group of patients who may benefit most. Follow-up revealed similar recurrences after APBI and whole breast irradiation (WBI), but cosmesis results were better after partial breast irradiation. These studies indicated that APBI may prove to be a significant advance in the treatment of selected patients with early-stage breast cancer